Optimalisasi Manajemen Downtime pada SIMRS dan REM di RSUD dr. R. Goeteng Taroenadibrata Purbalingga - Muhammad, Kukuh; Fajar Mahardika; Rahmawan Bagus Trianto; Joko Purwanto (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
Guidance in managing downtime in the Hospital Management Information System (SIMRS) and Electronic Medical Records (RME) is a strategic step to maintain operational continuity and the quality of healthcare services at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. Recurrent downtime negatively impacts administrative processes and medical services, necessitating systematic and continuous management. This study aims to provide technical guidance in managing downtime and to enhance the understanding and skills of human resources, particularly the Information Technology (IT) team and users of SIMRS and RME. The methods employed include technical training, identification of downtime causes, development of system maintenance procedures, and capacity building for users in operating the information systems. The results indicate that structured training and technical support can reduce downtime frequency and accelerate responses to technical disruptions. These findings highlight the importance of strengthening the IT team through ongoing training, more systematic system maintenance planning, and the establishment of clear, user-friendly operational procedures. Continuous guidance is expected to improve the effectiveness of downtime management and support the smooth delivery of healthcare services. This effort is an integral part of enhancing the quality of information systems and advancing digital transformation in healthcare services.